Urban-rural water cycle and environmental health: systemic interrelations and strategies for resilient services in climate change contexts - Nudelman, Mario Alejandro; Bach, Fernando Diego (O Mundo da Saúde, 2025)
Case study based on observations carried out at CEGELAH over a 16-year period, promoting research, innovation, and technology transfer aimed at strengthening the planning capacities of small- and medium-scale drinking water services in the province of Entre Ríos. There are four levels of interrelations between the internal and external aspects of water supply systems. The objective is to identify areas of intervention in terms of innovations that can counteract the main vulnerabilities detected at this scale of services in a context of climate change. The first level involves understanding the urban/rural water cycle as a complex system, highlighting the scientific approach provided by General Systems Theory as an interdisciplinary language that enables the parts to be addressed not in isolation, but in interrelation. A second relational level is the expansion of the knowledge base through the participation not only of specialists, but also of key social actors in formulating this systemic understanding of the issues and in grounding the design of consensus-based action strategies. A third level consists of inclusive possibilities for rural sectors as beneficiaries with equal rights to urban users of the water supply. And a fourth relational level concerns the formation of public-private partnerships that progressively shape the water value chain, fostering synergies among the public water service, local governments, the scientific-technological system, suppliers of materials, equipment and services, professionals in the sector, laboratories, etc.